(untitled) (Singapore, 1998)
Deals with the theoretical and experimental investigation of the phase transitions which occur in complex fluid systems, namely lyotropic systems, microemulsions, colloids, gels, polymers, biological membranes, Langmuir monolayers and ferrofluids. The text contains 20-odd review papers from contributors to this field of research, summarizing the main results obtained in the description and understanding of the phase transitions taking place between the isotropic, nematic, cholesteric, lamellar, hexagonal and cubic mesophases of complex fluids.
Keywords: Complex fluids,Phase transformations (Statistical physics),Phức chất,Biển đổi pha (thống kê vật lý)